The Use of Mobile Technology in Addressing Medication Adherence: A Mixed Methods Study - Chanane, Nawal (Auckland University of Technology, 2021)
It has been estimated that every year in New Zealand, hundreds of thousands of medicines are dispensed to patients but never used. Ensuring patients’ adherence to prescribed medication is a significant challenge, and lack of Medication Adherence (MA) creates a burden on the overloaded healthcare system. Studies have reported that MA is estimated to cause at least 10% of unplanned hospitalisations and approximately 125,000 deaths annually in the US alone. Recent studies have highlighted the role of technology in providing interventions that contribute to MA. The most common technological interventions to assist MA fall under the umbrella of digital technology like text messaging, voice calls, mobile applications and digital pill boxes. However, the efficacy of these solutions varied from one study to another for several reasons, including variations in users’ acceptance, performance expectancy, and facilitating conditions that lead to low usage or abandonment and, therefore, a lack of sustainability. What remains unclear is the role of end-users and the factors that contribute to the usage of these types of technologies. Our research aims to investigate the use of digital technology in addressing medication adherence. This thesis has four primary objectives: (1) to investigate the perceptions of multidisciplinary experts (e.g. health providers, health system designers and health informatics researchers) in New Zealand on mHealth interventions in addressing MA; (2) to co-design and develop a mobile app Minimum Viable Product (MVP) based on the theoretical investigation; (3) to evaluate the MVP with end-users through focus-groups; and (4) to assess the feasibility, acceptability and efficacy of the MVP by end-users through a pilot study. To achieve our aims, we followed a Design Science Research (DSR) methodology, and a complex mixed-methods design was implemented to include the integration of multiple forms of data collection at different stages of the study (i.e. questionnaires, interviews, focus groups and a pilot study) as well as multiple forms of data analysis (grounded theory, descriptive statistics, statistical analysis) to answer the research questions. The results from the quantitative study (questionnaire) informed the qualitative study (interviews and focus groups), which in turn validated the qualitative results. Purposeful sampling was utilised throughout the phases of the study. Descriptive and exploratory data analyses were performed for the quantitative data and inductive thematic analysis for the qualitative data. The findings of the quantitative and qualitative parts of the study were mixed and integrated at different points of the DSR methodology. The results show that four main features contributed to improving MA: (1) medication reminders using multi-channel notifications; (2) medication intake acknowledgement and history reporting; (3) auto-loading of medication; and (4) caregiver involvement. These novel features remained significant when built into the MVP and benefited the end-users in improving their medication intake during the pilot. This study confirmed that mHealth could have a significant impact on improving MA. Our findings from the rigorous iterative design process with end-users produced novel results validated through the trial by end-users. This work indicated that medication management applications could gain and sustain high usage, when integrated with an extensive digital health system, and can successfully keep the patient at the centre of care, connected and informed.
Keywords: Information system; Mixed methods; mHealth; Medication adherence; Grounded Theory; Focus group; Pilot study; Mobile interventions